Income perspective on the factors influencing households’ recycling intention: implications from the extended theory of planned behaviour - Khalil, Muhammad Salisu; Ho, Yuek Ming; Abd Manaf, Latifah; Sharaai, Amir Hamzah; Nabegu, Aliyu Baba (Malaysian Institute of Planners, 2019)
Although few studies have attempted to explain residents’ waste handling behaviour from social and psychological perspective, yet, there is little understanding regarding the influence of households’ moral obligation, consequences awareness, and perceived lack of facilitating conditions on forming recycling intention. This study aims at investigating the key determinants of household recycling intention using the extended theory of planned behaviour (TPB). Data collected from 422 households in Kano metropolis were analysed using structural equation modelling to determine the influence of each predictor on the recycling intention. The results indicate that attitude, subjective norms, personal norm, consequences awareness and perceived lack of facilitating conditions significantly predict recycling intention, with attitude being the most significant predictor of households’ intention. Additional analysis on the effect of households’ income level on their recycling intention shows that income level moderates the relationships between attitude and recycling intention, personal norms—recycling intention, and perceived lack of facilitating conditions—recycling intention. The findings provide valuable suggestions for recycling policies that can focus on households’ intention formation by providing recycling facilities, encouraging participation through market-driven recycling programs, and promoting recycling awareness and education